Pathogenic variants of Valosin‐containing protein induce lysosomal damage and transcriptional activation of autophagy regulators in neuronal cells. (15th May 2022) - Ferrari, Veronica; Cristofani, Riccardo; Cicardi, Maria E.; Tedesco, Barbara; Crippa, Valeria; Chierichetti, Marta; Casarotto, Elena; Cozzi, Marta; Mina, Francesco; Galbiati, Mariarita; Piccolella, Margherita; Carra, Serena; et al.
Abstract: Aim: Mutations in the valosin‐containing protein ( VCP ) gene cause various lethal proteinopathies that mainly include inclusion body myopathy with Paget's disease of bone and frontotemporal dementia (IBMPFD) and amyotrophic lateral sclerosis (ALS). Different pathological mechanisms have been proposed. Here, we define the impact of VCP mutants on lysosomes and how cellular homeostasis is restored by inducing autophagy in the presence of lysosomal damage. Methods: By electron microscopy, we studied lysosomal morphology in VCP animal and motoneuronal models. With the use of western blotting, real‐time quantitative polymerase chain reaction (RT‐qPCR), immunofluorescence and filter trap assay, we evaluated the effect of selected VCP mutants in neuronal cells on lysosome size and activity, lysosomal membrane permeabilization and their impact on autophagy. Results: We found that VCP mutants induce the formation of aberrant multilamellar organelles in VCP animal and cell models similar to those found in patients with VCP mutations or with lysosomal storage disorders. In neuronal cells, we found altered lysosomal activity characterised by membrane permeabilization with galectin‐3 redistribution and activation of PPP3CB. This selectively activated the autophagy/lysosomal transcriptional regulator TFE3, but not TFEB, and enhanced both SQSTM1/p62 and lipidated MAP1LC3B levels inducing autophagy. Moreover, we found that wild type VCP, but not the mutants, counteracted lysosomal damage induced either by trehalose or by a mutant form of SOD1 (G93A), also blocking the formation of its insoluble intracellular aggregates. Thus, chronic activation of autophagy might fuel the formation of multilamellar bodies. Conclusion: Together, our findings provide insights into the pathogenesis of VCP‐related diseases, by proposing a novel mechanism of multilamellar body formation induced by VCP mutants that involves lysosomal damage and induction of lysophagy. Abstract : We investigated the impact of VCP mutants, on lysosomes and on autophagy showing that they, like other misfolded proteins, trigger the formation of multilamellar bodies from damaged lysosomes with morphological alterations, decreased acidification and impaired enzyme activity. This resulted in membrane permeabilisation with galectin‐3 redistribution and specific PPP3CB‐mediated activation of TFE3, but not of TFEB, which positively regulates autophagic flux. Thus, chronic autophagy activation might fuel the formation of multilamellar bodies, but this mechanism is counteracted by VCP wt modulation.